Peningkatan Prestasi Belajar Pendidikan Agama Islam Melalui Penerapan Card Sort Learning - Nur Fadilah (Nadwa: Jurnal Pendidikan Islam, 2017)
Appropriate learning methods should be applied in order to maximize the students’ ability during learning activities. The purpose of this study is to determine the improvement of learning achievement of Islamic Religious Education (PAI) through the application of card sort learning method. Action study conducted on PAI learning. The material of this learning is to  understand the provision of sholat of fourth graders of Gunungsari State Elementary School 2 Kaliori Sub district Rembang District Lesson Year 2015/2016. The indicator of successful learning in this research is 75%. The results showed that the percentage of learning mastery at the pre cycle stage was 10.7%, 67.9% in the first cycle, and in the second cycle reached 92.9%. The average score of students' test results also increased significantly, ie the pre cycle stage was 58.8, the first cycle was 72.4, and in the second cycle reached 78.9. This means, through the implementation of card sort learning methode can improve student learning achievement on PAI learning material understanding the provision of sholat.  lAbstrakMetode pembelajaran yang tepat harus diterapkan untuk memaksimalkan kemampuan siswa selama kegiatan pembelajaran. Penelitian ini bertujuan untuk mengetahui peningkatan prestasi belajar Pendidikan Agama Islam (PAI) melalui penerapan metode card sort. Studi tindakan (action research) dilakukan pada pembelajaran PAI materi mengenai rukun sholat siswa kelas IV Sekolah Dasar Negeri Gunungsari 2 Kecamatan Kaliori Kabupaten Rembang Tahun Pelajaran 2015/2016. Indikator eHasil penelitian menunjukkan bahwa persentase ketuntasan belajar pada tahap pra siklus sebesar 10,7%, pada siklus I sebesar 67,9%, dan pada siklus II mencapai 92,9%. Nilai rata-rata hasil tes siswa juga mengalami peningkatan yang signifikan, yaitu para tahap pra siklus sebesar 58,8, siklus I sebesar 72,4, dan pada siklus II naik menjadi 78,9. Hal ini berarti, melalui penerapan card sort learning dapat meningkatkan prestasi belajar siswa pada pembelajaran PAI materi mengenal rukun sholat.